A importância sistemática do Sumo Bem como operador de passagens e da unidade da razão pura em Kant - Cortes, Rafael da Silva (2018)
The following research aims to support the idea that the concept of the Highest Good has an important role within the systematic totality of Kant‟s philosophy. For this purpose, we focus mainly on the works by the author himself as well as in studies of renowned scholars of the Kantian philosophy. Throughout this study, arguments and counter-arguments about the positions presented have been exposed with the intention of making the thesis of this work clear, consistent and valid. In order to do so, at first, Kant‟s main arguments about his critical-transcendental theory – which stated purpose was to undertake a detailed analysis of the human cognitive capacities, and thus to demonstrate the possible conditions for us to debate about the human knowledge in a legitimate way – were rebuilt. Therefore, the arguments and the key elements of his moral theory were presented, especially the concept of the Highest Good which is considered by the author as the unconditional object of pure reason as far as it brings together the cardinal concepts of metaphysics: God, immortality of the soul and freedom. The above-mentioned concept is formed by two elements, morality or virtue as the human expectation of being morally happy, and the establishing of happiness according to one‟s moral merit. In addition, we analyzed the principle of purposiveness and the power of reflective judgment through which, according to Kant, we can think of nature as having its own ends, in other words, as if it was organized as a living organic system. It has been shown that it is also due to the power of reflective judgment and its a priori principle of purposiveness that we think of the Highest Good as the final end of nature. Finally, the main thesis presented in this work is supported through three arguments: the first one affirms that the Highest Good is systematically relevant to the totality of Kant‟s philosophical project and not only to its specific stages, such as his moral philosophy; The second one is that the systematic importance of this concept arises from the fact that through it the author operates different passages and units in his philosophical theory; Lastly, the third argument in favor of the proposition of this research states that the most important passage operated by the Highest Good concerns the different stages of the philosophical exposition of Kant and that so the author sheds new light on the possibility of the metaphysics to acquire philosophical-scientific status.